Semantic validation of educational technology with caregivers of children and adolescents undergoing chemotherapy - Silmara de Oliveira Silva; Thamyres Alany Campelo de Araújo; Naryllene Maciel de Araújo; Nahadja Tahaynara Barros Leal; Fernando Hiago da Silva Duarte; José Eugênio Lopes Leite; Rodrigo Assis Neves Dantas; Daniele Vieira Dantas (Associação Brasileira de Enfermagem, 2022)
ABSTRACT Objective: Semantically validate an educational technology with the caregiver of children and adolescents undergoing chemotherapy. Method: Methodological study, with a quantitative approach, guided by the theoretical framework of psychometry, developed between March and April 2022, with nine caregivers of children and adolescents undergoing chemotherapy. Educational technology is a digital animation film about the pediatric chemotherapy treatment process, used as a tool for health education. Results: In the reliability assessment, the Intraclass Correlation Coefficient was 0.936 [95%CI 0.868-0.984] with p < 0.05 and Cronbach's alpha of 0.943, demonstrating satisfactory internal consistency. Regarding the semantic analysis, the domains related to objectives, organization, language, appearance, and motivation showed an agreement rate above 80%. Conclusion: Educational technology showed satisfactory rates, proving to be a valid, reliable, and important instrument to be used by caregivers of children and adolescents undergoing chemotherapy.